Biomedical Engineering and Design Handbook, Volume 2 - Kutz, Myer (McGraw-Hill Education, 2009)
A cutting-edge guide to new medical devices and equipment, surgical and therapeutic techniques, and clinical innovations. Biomedical engineering is the application of engineering principles and techniques to the medical field. The two-volume Biomedical Engineering and Design Handbook offers you unsurpassed coverage of the entire biomedical engineering field,including the fundamental concepts, design processes and procedures, and applications. This landmark work contains contributions on a wide range of engineering and design problems from over 40 leading experts at universities and medical centers around the globe. Volume II provides a wealth of timely information on breakthrough developments in medical device design, diagnostic equipment design, therapy and surgery, rehabilitation and prosthetic design, and the clinical engineering of healthcare facilities. Packed with 400 instructive illustrations, this indispensable volume provides you with detailson new design methods for cardiovascular and respiratory devices, imaging instrumentation, artificial limbs, healthcare facilities planning, and much more.